Manufacture of Grass Cutting Machine for Efficiency of Making Ruminant Animal Feed Preparation in Kebonharjo Village Jatirogo District Tuban Regency - Hesti Kurniahu; Krishna Tri Sanjaya; Arik Umi Pujiastuti (ASEAN Journal of Empowering Community, 2021)
Feed preparations are the most important thing in the field of animal husbandry. This activity is done every day and often takes a lot of time and effort, especially if done manually and to meet the needs of feed on livestock in large quantities. This obstacle is felt by breeders who are in the Kebonharjo Village Jatirogo district of the Tuban regency. To overcome this, it is necessary to conduct a Community Service program to hold feed kits for ruminant animals and provide knowledge in the efficiency of time and animal feeder personnel. Partners in this community service program are two farmers in Kebonharjo Village of Jatirogo District of Tuban Regency, with more than 15 cattle. In this program, the approach is to conduct direct observations and interviews to get data and problems faced by partners and to offer solutions that who will give to help partner problems. The solution provided by Tim community service is to hold an Electric and Portable Feed Countering tool (PPEP) so that the activities of providing animal feed by partners are more effective and efficient.